Analisis Guessability Score dan Pemahaman Piktogram Kefarmasian pada Pasien Tuberkulosis - Ema Rachmawati; Dhea Nanda Aliefia; Fransiska Maria Christianty (Jurnal Ilmiah Farmasi, 2023)
Background: Pharmaceutical pictograms can be used to help tuberculosis patients understand treatment information, especially those with low reading skills.Objective: This study aimed to analyze the guessability score and the level of understanding of pharmaceutical pictograms related to the use of TB drugs.Method: This was an observational study with a cross-sectional design. The sample used was 96 TB patients who were actively undergoing treatment. The guessability score and level of understanding were analyzed descriptively, while the relationship between socio-demographic characteristics and the level of understanding of pharmaceutical pictograms was analyzed using the Chi-square test.Results: The results showed that the guessability score of 23 pictograms tested on respondents varied greatly, with a score range of 29.2%â€“99%. Meanwhile, the level of respondents' understanding of pharmaceutical pictograms related to TB treatment was in the "fair" category. The Chi-square test showed a significant relationship between the level of respondentsâ€™ education and their understanding of pharmaceutical pictograms.Conclusion: The findings of this study demonstrated that not all pictogram images were simple for respondents to understand. It is necessary to choose pictogram images that are easy for respondents to understand or redesign pictogram images so that they can be used to improve the effectiveness of drug information delivery to patients. Intisari Latar belakang: Gambar piktogram kefarmasian dapat digunakan untuk membantu pasien tuberkulosis memahami informasi pengobatan, khususnya untuk pasien dengan tingkat literasi rendah. Tujuan: Penelitian bertujuan untuk mengukur kemampuan menerka (guessability score) dan pemahaman responden terhadap piktogram kefarmasian terkait pengobatan tuberkulosis.Metode: Penelitian observasional cross-sectional terhadap 96 responden pasien TB yang aktif menjalani pengobatan. Guessability score dan tingkat pemahaman dianalisis secara deskriptif, sedangkan hubungan karakteristik sosio-demografi dengan tingkat pemahaman dianalisis dengan uji Chi-square.Hasil: Hasil penelitian menunjukkan kemampuan menerka (guessability score) terhadap 23 gambar piktogram sangat beragam, dengan rentang skor 29,2% â€“ 99%. Sedangkan tingkat pemahaman responden terhadap piktogram kefarmasian terkait pengobatan TB masuk dalam kategori â€œcukupâ€. Uji Chi-square menunjukkan adanya hubungan yang signifikan antara tingkat pendidikan terhadap tingkat pemahaman responden.Kesimpulan: Tidak semua gambar piktogram kefarmasian mudah dipahami oleh responden. Untuk itu perlu memilih gambar piktogram yang mudah dipahami reponden atau melakukan desain ulang gambar piktogram sehingga dapat digunakan untuk meningkatkan efektivitas pemberian informasi obat pada pasien.Kata kunci: guessability score, pemahaman, piktogram kefarmasian, tuberculosis